Up-regulation of long non-coding RNA BLACAT1 predicts aggressive clinicopathologic characteristics and poor prognosis of glioma. Issue 11 (19th March 2021) - Zhang, Xiaojue; Wei, Xiuchuan; Liu, Jie; Yang, Jiaying; Jin, Peng
Abstract : Abstract: Bladder cancer-associated transcript 1 (BLACAT1) is one of the most common cancer-associated long non-coding RNAs (lncRNAs), which has been reported as a tumor promotor in several malignancies. Previously, BLACAT1 was found to be overexpressed in glioma tissues and cell lines. Functional assays determined that BLACAT1 promoted glioma cell proliferation, migration, invasion and epithelial-mesenchymal transition, suggesting that BLACAT1 might serve as an oncogene in glioma. In the present study, we aimed to investigate its clinical significance and prognostic value in glioma patients. A total of 137 paired glioma tissue samples and adjacent normal brain tissue samples were collected from 137 glioma patients who underwent surgery from May 2014 to February 2019. The Student t test was applied to determine the statistical significance of the observed differences between 2 groups. Survival curves were constructed and differences among groups were calculated using the Kaplan–Meier method. The relative expression of BLACAT1 in glioma samples was significantly higher than that of matched normal tissues ( P < .001). The expression level of tissue BLACAT1 was statistically correlated with tumor size ( P = .04), Karnofsky Performance Status (KPS) ( P = .006), and WHO grade ( P = .017). Kaplan–Meier analysis with the log-rank test revealed that BLACAT1 up-regulation was correlated with shorter overall survival time of patients with glioma (Log Rank test, P = .012). In multivariate Cox analysis, BLACAT1 expression was found to be an independent prognostic factor for overall survival in patients with glioma (HR = 2.739; 95% CI: 1.785–8.229; P = .035). Our study demonstrates that up-regulation of BLACAT1 is able to predict aggressive clinicopathologic characteristics and poor prognosis of glioma patients. These findings may have significant implications for potential treatment options and prognosis for patients with glioma.